Analisis Peran Guru dalam Mewujudkan Sekolah Ramah Anak di Kecamatan Kediri - Ahmad Najihi Fathu Rozik; Nurhasanah; Gozin Najah Rusyada (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study analyzes the role of teachers in establishing Child-Friendly Schools (SRA) in Kediri Subdistrict, identifies the supporting and inhibiting factors faced, and describes their efforts to overcome these obstacles. This qualitative descriptive study was conducted at SDN 1 Montong Are, SDN 1 Jagaraga Indah, and SDN 3 Banyumulek, West Lombok Regency, with 3 principals, 6 teachers, and 9 students as informants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, while validity was tested through source and methodological triangulation. The results show that teachers act as facilitators, mentors, and motivators. As facilitators, they apply active and varied methods; as mentors, they provide individual guidance, instill positive discipline, and handle misconduct without violence; and as motivators, they give recognition and opportunities to build students’ self-confidence. Supporting factors include a conducive school environment, teachers’ understanding of SRA, and synergy among school, family, and community, whereas inhibiting factors include the family environment and low parental involvement. Teachers address these obstacles by strengthening communication with parents, adjusting their approaches, and fostering cooperation. The study underlines stronger school–family–community collaboration and enhanced teacher competence for optimal, sustainable SRA implementation.